Training and assistance in marketing agricultural products for the Humbahas community - Andrasari, Monika; Anggia, Yola; Simatupang, Dewi Ratna Sari; Hasibuan, Widya Sartika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to improve the welfare of the farming community in Humbang Hasundutan, especially farmers in Ria-Ria Village, Pollung District through marketing using online media. Farmers must be able to adapt to technological developments, and must be able to access the latest information related to agriculture and marketing, where utilizing digital media is a challenge for them. This service method is carried out by socializing, training to operate a website, creating a marketing account and how to start selling through one of the leading marketplaces. The results of this service are expected to contribute to improving the economy of the farmers in the Humbahas food estate and to introduce their agricultural products more broadly to the entire community.